Gastric Cancer Screening Methods: A Comparative Study of Two Scoring Methods - Zhang, Weixing (Cancer Manag Res, 2021)
OBJECTIVE: To evaluate the Li’s and Japanese scoring methods scoring for screening early gastric cancer in a healthy population. METHODS: During January 2016–December 2018, profiles of the healthy people participated in a physical examination in the first people’s Hospital of Shanghai were collected. A total of 342 volunteers, including 137 males and 205 females ageing 40–74, were enrolled. After recording the basic information, all volunteers were scored using the Japan scoring method and the new gastric cancer screening score (ie, Li’s score). The subjects’ work characteristics (ROC curve) were drawn according to the patient’s endoscopic pathological examination to indicate early gastric cancer, to determine the best cut-off point for the diagnosis of early gastric cancer by Japanese scoring and Li’s scoring, respectively. The sensitivity and specificity of both scoring methods were calculated as well. RESULTS: The area under the ROC curve of Japanese and Li’s score, in the diagnosis of early gastric cancer, was 0.763 and 0.837, respectively. Japanese and Li’s score ≥14 were considered as the best cut-off point. The sensitivity and specificity of Li’s scoring were 63.60% and 91.10%, respectively. The sensitivity and specificity of the Japanese score were 54.50% and 87.50%, respectively. The area under the ROC curve in Li’s scoring is more significant than that in Japanese scoring, and there was a substantial difference in the two methods (P<0.05). CONCLUSION: Both Li’s scoring and Japanese scoring have shown good screening value for early gastric cancer in a healthy population, but Li’s scoring is more sensitive/specific than Japanese scoring.